Role of the hospital pharmacists during COVID-19 pandemic in the RN Macedonia - Zorica Naumovska; Biljana Lazarova; Maja Kovaceva; Aleksandra Kapedanovska Nestorovska; Maja Simonoska Crcarevska; Evgenija Mihajloska; Aleksandar Dimkovski (Makedonsko Farmacevtski Bilten)
Hospital pharmacists played a crucial role during the COVID-19 pandemic, collaborating with healthcare professionals such as nurses, physicians, and respiratory therapists. They contributed to managing COVID-19 treatment protocols, ensuring adequate medication supply, and addressing shortages of essential drugs, medical devices, and personal protective equipment (PPE) by implementing conservation strategies and sourcing alternatives. A questionnaire-based study was conducted among hospital pharmacists in North Macedonia in July 2022, involving pharmacists and pharmacy technicians of various ages and experience levels from five cities, with 95.8% of respondents being female. The results highlighted the pharmacists' knowledge of COVID-19 strains, disinfectants, and current therapeutic options. The study revealed that 37.5% of participants always, 20.8% frequently, and 29.2% occasionally felt depressed or fatigued during the pandemic, though 83% never considered leaving their jobs. The survey found that 87.5% of pharmacists experienced shortages of masks, gloves, and disinfectants early in the pandemic, and 100% noted the increased cost of these supplies. Only 22.7% were not consulted for therapy advice for hospitalized COVID-19 patients. Opinions varied on the use of off-label drugs, and pharmacists played a key role in pharmacovigilance practices, with 36.4% reporting adverse events. The study confirmed the vital role of hospital in promoting of rational antibiotic use and antimicrobial resistance programs. This study was the first study conducted after the pandemics and have confirmed the pivotal role of hospital pharmacists in this period in the RN Macedonia.